If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -51 + -1z = 51 Solving -51 + -1z = 51 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + -1z = 51 + 51 Combine like terms: -51 + 51 = 0 0 + -1z = 51 + 51 -1z = 51 + 51 Combine like terms: 51 + 51 = 102 -1z = 102 Divide each side by '-1'. z = -102 Simplifying z = -102
| 239.92=17.6c | | 3=n/7 | | 45-x=-16 | | 4ab+6ax-2b-3x= | | 7x+3(-x-4)=28 | | ln(2x)=-1/2 | | 4+4x=9-11 | | 2x+2.5y=450 | | 2b-6=8b | | -10n-29=-18n+21 | | 2-4(1/9)(x)=-6 | | 2x(x+3)=x-4 | | 3x+105= | | 5x-12=12x+10 | | 0.4x-5=0.08x+3 | | 6(8-5)-3squared= | | .9x-2.7=.9 | | 3/12x=2=11 | | 4x-(x+3)=-16 | | 10(j+1)=100 | | 2(3.5*3.11+6)=2.5*3.11-2 | | -2(5t-5)+8t=2t-5 | | y+7=4(y-2) | | 5x(2x+1)=50 | | 3u-20=13 | | 0=(x^2)-4x+2 | | X-5(x-3)=2(x-10) | | 29.75m+0.15p=19.95m+0.29p | | 3(3-1)=4(3-15) | | 20=a/-4 | | 4(12.5-2)=3(1.5+12.5) | | 1x-3=6 |